PENGARUH KOMPETENSI, PENDIDIKAN AUDITOR, PENGALAMAN AUDITOR, DAN LAMANYA HUBUNGAN AUDIT TERHADAP INDEPENDENSI AUDITOR (Studi Empiris pada KAP di Kota Medan, Pekanbaru, dan Padang) - Miftakhul Hidayah; Amir Hasan; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the influence of the competency, auditors education, auditors experience and the length of the audit relationship on the Auditors Independency. Auditors independency has a very important role to the auditor when the audit task is to maintain an honest and impartial attitude to anyone.The population in this study is the auditor who worked on the KAP Medan, Pekanbaru, and Padang consisting of 34 KAP. The samples used by random sampling. Questionnaire distributed to respondents were 170 and the number of questionnaires that can be analyzed as many as 95. The data analysis technique used in this study is the technique of multiple regression analysis by using SPSS version 20.0.The result of this study indicated that competency, auditors education, and auditors experience have significantly effect on auditors independency. While the length of audit relationship dont have significantly effect on auditors independency.Keywords: Competency, Auditors Education, Auditors Experience, The Length of Audit Relationship, and Auditors Independency.